2011
DOI: 10.1055/s-0031-1299941
|View full text |Cite
|
Sign up to set email alerts
|

Verminderung der Rezidivhäufigkeit bei Patienten mit chronisch rezidivierender hypertrophischer Sinusitis unter Behandlung mit einem bakteriellen Immunstimulans (Enterococcus faecalis-Bakterien humaner Herkunft)

Abstract: A double-blind, placebo-controlled multicenter study in 157 patients with chronic recurrent sinusitis investigated the occurrence of acute relapses during treatment of patients with a bacterial immunostimulant (3 x 30 drops/day), comprised of cells and autolysate of human Enterococcus faecalis bacteria (Symbioflor 1, n = 78) in comparison to placebo (n = 79). The study included a treatment period of 6 months and a follow-up period of 8 months. Under verum the occurrence of relapses (50 incidents) was about hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 6 publications
0
26
0
1
Order By: Relevance
“…In contrast to antibiotics, probiotics can reverse the diversity of the sinus microbiome [ 54 ]. Oral probiotic administration is beneficial in treating CRS [ 55 ], reducing colonization of pathogenic species [ 56 ], and preventing upper respiratory tract infections [ 57 ]. These studies indicated the important roles of dental hygiene and oral microbiome in CRS.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to antibiotics, probiotics can reverse the diversity of the sinus microbiome [ 54 ]. Oral probiotic administration is beneficial in treating CRS [ 55 ], reducing colonization of pathogenic species [ 56 ], and preventing upper respiratory tract infections [ 57 ]. These studies indicated the important roles of dental hygiene and oral microbiome in CRS.…”
Section: Discussionmentioning
confidence: 99%
“…The use of oral Enterococcus faecalis showed benefit in treating CRS and recurrent acute rhinosinusitis in two studies. 65 , 66 The benefit was seen to last for up to 8 months in one randomized study in which probiotic was administered for 6 months. 65 Although the use of probiotics is well described in gastrointestinal research, the use in CRS remains limited.…”
Section: Chronic Rhinosinusitis and Microbiomementioning
confidence: 99%
“…Now, probiotics can be considered as a therapeutic option for treatment of allergy and even for inducing or maintaining clinical remission of IBS. E. faecalis Symbioflor 1, an immunomodulatoty strain, has been used to combat recurrent, chronic sinusitis or bronchitis and to help to asthma treatment in school children ( 22 , 23 ). E. faecium Paraghurt ® has demonstrate its efficacy in lowering the symptoms associated with IBS in a clinical study ( 24 ) as well as E. faecium PR88 ( 25 ) and the multi-strains probiotic ProSymbioflor ® ( E. faecalis and E. coli ) ( 26 ).…”
Section: Introductionmentioning
confidence: 99%